ANALISIS PENERAPAN IN HOUSE TRAINING (IHT) DALAM MENINGKATKAN KOMPETENSI GURU DAN KETERLIBATAN SISWA DALAM PEMBELAJARAN DI SDIT COKROAMINOTO - Rohmayanti, Salsa; Jenal Mutaqin, Ejen; Nadiroti Muslihah, Neni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the suboptimal learning process at SDIT Cokroaminoto, which is characterized by low student engagement, less conducive classroom conditions, and limited teacher competency. This study aims to analyze the implementation of In-House Training (IHT) in improving teacher competency and its impact on student engagement. This study uses a qualitative approach with a descriptive analytical research type. Data were collected through observations and interviews with the principal and sixth – grade teachers. Then, they were analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results show that IHT is effective in improving teacher pedagogical competency, especially in classroom management. In addition, the implementation of varied learning strategies through IHT can also increase student engagement. IHT also strengthens collaboration between teachers, which helps improve the quality of learning. Thus, IHT is a teacher professional development program that is relevant, contextual, and has a positive impact on the quality of learning in elementary schools.